Comparison of two non-destructive techniques to determine DM yield in the tropics - Villalobos Villalobos, Luis Alonso (2018)
Dry matter yield determines both stocking rate and animal carrying capacity on farms, but to estimate such indicators, accurate yield measures are required. Some common techniques to estimate biomass in pastures are cumbersome, which makes producers reluctant to undertake measurement. In temperate grazing systems, use of plate meter devices has improved frequency of measurement. However, plate meter calibration equations were developed with temperate grasses (i.e. ryegrass, fescue, etc), and their use in the tropics thus far is limited and has not been evaluated. In this study, we estimated biomass across one year with both the Botanal® technique and a rising platemeter in Costa Rica, focusing on perennial ryegrass (Lolium perenne), Kikuyu (Kikuyuocloa clandestina), and African Stargrass (Cynodon nlemfuensis) pastures. Estimates of DM yield made with a plate meter were higher than with the Botanal® technique, especially in ryegrass (1,553 kg DM ha-1), but also in Kikuyu (720 kg DM ha-1) and Stargrass (683 kg DM ha-1) pastures. Calibration of the plate meter with the regression equations developed in this study may improve accuracy with grasses grown in the tropics. Such straightforward techniques for biomass estimation could improve adoption by producers on tropical farms.